Overleveraging, financial fragility and the banking-macro link: Theory and empirical evidence - Stefan Mittnik; Willi Semmler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We investigate consequences of overleveraging and financial-sector stress on real economic activities. When banks become vulnerable, due to high leveraging, and there is a strong feedback between the real and the financial sector, a regime of high financial stress may arise. The vulnerability of the banking system in a high lever- age and a high-stress regime can, through macro feedback effects, result in unstable dynamics. To assess this question empirically, we employ a nonlinear, multi-regime vector autoregression approach (MRVAR), to explore the consequences of instabilities arising from regime dependent shocks. We analyze data on industrial production and the IMF Financial Stress Index. In order to assess how output is affected by the individual risk drivers making up the IMF index, we study eight economies - the U.S., Canada, Japan and the UK, and for the four largest euro-zone economies, namely, Germany, France, Italy, and Spain -, using Granger-causality and nonlinear impulse-response analysis. Our results strongly suggest that financial-sector stress, exerts a strong, nonlinear influence on economic activity, but that individual risk drivers affect economic activity rather differently across stress regimes and across countries.
urn:nbn:de:bsz:180-madoc-374554
Keywords: E2; E6; C13; 330